একবিংশ শতাব্দীতে রবীন্দ্রচর্চা ও অন্যান্য প্রবন্ধ - ডাইসন, কেতকী কুশারী, ১৯৪০-
Articles chiefly on studies that came up on the life and works of Rabindranath Tagore, 1861-1941, Bengali author, since 1950, from West Bengal and other places in India and outside India, which could be trend-setters for research on him in the 21st century.